Controlling the formation of ionic-liquid-based aqueous biphasic systems by changing the hydrogen-bonding ability of polyethylene glycol end groups - Pereira, Jorge F. B. [UNESP]; Kurnia, Kiki A.; Freire, Mara G.; Coutinho, João A. P.; Rogers, Robin D. (Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim, 2015)
The formation of aqueous biphasic systems (ABS) when mixing aqueous solutions of polyethylene glycol (PEG) and an ionic liquid (IL) can be controlled by modifying the hydrogen-bond-donating/-accepting ability of the polymer end groups. It is shown that the miscibility/immiscibility in these systems stems from both the solvation of the ether groups in the oxygen chain and the ability of the PEG terminal groups to preferably hydrogen bond with water or the anion of the salt. The removal of even one hydrogen bond in PEG can noticeably affect the phase behavior, especially in the region of the phase diagram in which all the ethylene oxide (EO) units of the polymeric chain are completely solvated. In this region, removing or weakening the hydrogen-bond-donating ability of PEG results in greater immiscibility, and thus, in a higher ability to form ABS, as a result of the much weaker interactions between the IL anion and the PEG end groups.
Keywords: Aqueous biphasic systems; Hydrogen bonding; Ionic liquids; Polyethylene glycol; Polymers